Critical role for the NLRP3 inflammasome during acute lung injury - Grailer, Jamison J.; Canning, Bethany A.; Kalbitz, Miriam; Haggadone, Mikel D.; Dhond, Rasika M.; Andjelkovic, Anuska V.; Zetoune, Firas S.; Ward, Peter A. (Journal of Immunology, 2014)
The inflammasome is a key factor in innate immunity and senses soluble pathogen and danger-associated molecular patterns as well as biological crystals (urate, cholesterol, etc.), resulting in expression of IL-1β and IL-18. Using a standard model of acute lung injury (ALI) in mice featuring airway instillation of LPS, ALI was dependent on availability of NLRP3 as well as caspase-1, which are known features of the NLRP3 inflammasome. The appearance of IL-1β, a product of NLRP3 inflammasome activation, was detected in bronchoalveolar lavage fluids (BALF) in a macrophage- and neutrophil-dependent manner. Neutrophil-derived extracellular histones appeared in the BALF during ALI and directly activated the NLRP3 inflammasome. Ab-mediated neutralization of histones significantly reduced IL-1β levels in BALF during ALI. Inflammasome activation by extracellular histones in LPS-primed macrophages required NLRP3 and caspase-1 as well as extrusion of K+, increased intracellular Ca2+ concentration, and generation of reactive oxygen species. NLRP3 and caspase-1 were also required for full extracellular histone presence during ALI, suggesting a positive feedback mechanism. Extracellular histone and IL-1β levels in BALF were also elevated in C5ainduced and IgG immune complex ALI models, suggesting a common inflammatory mechanism. These data indicate an interaction between extracellular histones and the NLRP3 inflammasome, resulting in ALI. Such findings suggest novel targets for treatment of ALI, for which there is currently no known efficacious drug. Copyright © 2014 by The American Association of Immunologists, Inc. 0022-1767/14/16.
CRIS-Team Scopus Importer:2020-12-21